2018
DOI: 10.1002/cld.721
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Nonalcoholic Fatty Liver Disease and Cardiovascular Disease Outcomes

Abstract: http://aasldpubs.onlinelibrary.wiley.com/hub/journal/10.1002/(ISSN)2046-2484/video/12-2-reading-wong a video presentation of this article https://www.wileyhealthlearning.com/Activity/6554145/disclaimerspopup.aspx questions and earn CME

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
1
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 23 publications
0
37
1
3
Order By: Relevance
“…Dyslipidemia (high serum triglyceride, decreased serum high-density lipoprotein levels, increased serum low-density lipoprotein) is also a well-established risk factor for NAFLD, which has an estimated overall prevalence of 53.8% of patients attending lipid clinics, and 78.0% among the subgroup with the highest total cholesterol to high-density lipoprotein cholesterol or triglyceride to high-density lipoprotein cholesterol ratios. 65 Among patients with NAFLD, dyslipidemia is associated with an increased risk of NASH and cardiovascular disease, [65][66][67] but has not been demonstrated to represent an independent risk factor for liverrelated mortality. 66,67 Recent data suggest a possible association between hyperlipidemia and HCC incidence in noncirrhotic patients with biopsy-proven NASH.…”
Section: Best Practice Advice 7: Optimal Management Of Diabetes and Dmentioning
confidence: 99%
See 1 more Smart Citation
“…Dyslipidemia (high serum triglyceride, decreased serum high-density lipoprotein levels, increased serum low-density lipoprotein) is also a well-established risk factor for NAFLD, which has an estimated overall prevalence of 53.8% of patients attending lipid clinics, and 78.0% among the subgroup with the highest total cholesterol to high-density lipoprotein cholesterol or triglyceride to high-density lipoprotein cholesterol ratios. 65 Among patients with NAFLD, dyslipidemia is associated with an increased risk of NASH and cardiovascular disease, [65][66][67] but has not been demonstrated to represent an independent risk factor for liverrelated mortality. 66,67 Recent data suggest a possible association between hyperlipidemia and HCC incidence in noncirrhotic patients with biopsy-proven NASH.…”
Section: Best Practice Advice 7: Optimal Management Of Diabetes and Dmentioning
confidence: 99%
“…65 Among patients with NAFLD, dyslipidemia is associated with an increased risk of NASH and cardiovascular disease, [65][66][67] but has not been demonstrated to represent an independent risk factor for liverrelated mortality. 66,67 Recent data suggest a possible association between hyperlipidemia and HCC incidence in noncirrhotic patients with biopsy-proven NASH. 68 Dyslipidemia is routinely treated with antilipidemic agents, such as statins, although limited data are available to clarify the impact of statins on clinical outcomes in patients with NAFLD.…”
Section: Best Practice Advice 7: Optimal Management Of Diabetes and Dmentioning
confidence: 99%
“…4,12,13 Adults with NAFLD have a 2-fold increased risk of coronary artery disease and have increased cardiovascular events. 14 Individuals with NAFLD also have a lipid profile referred to as the 'atherogenic lipid triad', typified by increased levels of low-density lipoprotein cholesterol (LDL-C) and triglycerides (TG), and low HDL-C. 15 A longitudinal community follow-up study in the USA showed an increasing incidence of NAFLD, particularly in adolescents and young adults, and an association between NAFLD and increased cardiovascular events over 10 years. 16 Remnant lipoprotein cholesterol (RLP-C), the cholesterol contained in very-low-density lipoprotein (VLDL), was associated with incident coronary heart disease in adults in the Jackson Heart and Framingham Offspring Cohort Studies in the USA.…”
Section: Introductionmentioning
confidence: 99%
“…(12,17,18) Thus, aggressive screening for metabolic and CVD risk factors as well as risk factor modification are essential strategies to reduce the risk of CVD mortality. (19) The European Association for the Study of the Liver (EASL) and American Association for the Study of the Liver Disease (AASLD) guidelines recommend screening for metabolic risk factors in patients with NAFLD; however, at this time there is no role for screening asymptomatic individuals with NAFLD for CVD. (1, 20) An algorithm to screen and manage metabolic risk factors, including obesity, diabetes, dyslipidemia, and hypertension, in patients with NAFLD, has been proposed by Wong and Lim.…”
Section: Cardiovascular Disease (Cvd)mentioning
confidence: 99%